Policy Analysis of the National Health Insurance Program in Budget Deficit Problems and Its Implication to guarantee patient Covid-19 - Ridwan, Asrifia (Jurnal Magister Administrasi Publik, 2021)
The purpose of this study is to analyze and describe the National Health Insurance program in terms of the budget deficit problem and its implications for health insurance for Covid-19 patients. This study uses a qualitative method oriented to library research (library research) using secondary data sources and William N. Dunn's analytical approach. The results of this study indicate that the National Health Insurance (JKN) program has not found a bright spot in dealing with the budget deficit after the JKN rate increase through Presidential Decree Number 75 of 2019 was canceled by the Supreme Court because it was considered to have violated the provisions of the 1945 Law article 28 H paragraph 1. The handling of covid-19 patients as the health insurance is instructed to be borne by the BPJS also has legal regulatory constraints, which is contrary to Presidential Decree Number 82 of 2018 article 52 paragraph 1 letter O. Even though the efforts to service covid-19 patients, the budget comes from injecting APBN and APBD funds as effort prevention of a larger deficit, but operationally violates applicable legal provisions. For this reason, it is necessary to make new rules and revise related regulations in order to accelerate the handling of policies in accordance with applicable legal provisions.